LOCAL COMMUNITIES COOPERATION IN CROSS-BORDER AREA OF UKRAINE AND THE EU - Tymechko , I. R. (The actual problems of regional economy development, 2017)
Border local communities has received additional financial resources in the conditions of European integration. The aim of the article is justification of the financial instruments of local communities cooperation in cross-border area of Ukraine and the EU. It was revealed that the cooperation of local communities in cross-border area is different in size, scope of activities, consolidation or institutionalization, ranging between consultation or selective cooperation (specific issue) and programs and the creation of joint institutions (committees, associations, working groups, etc.). It is offered to highlight the cooperation in cross-border area as a cross-border cooperation, transnational cooperation and interregional cooperation. The European Union provides financial support to the cross-border cooperation through using of a number of initiatives, programmes and projects, namely: INTERREG, PHARE CBC, TACIS CBC, PHARE CREDO, MEDA, CARDS, LACE. The European neighbourhood and partnership instrument facilitates the economic and deeper political cooperation, provides the assistance for using the specific opportunities and solving territory problems that have the only border with the EU or that are geographically close to the neighboring countries of the EU.